ВОЗМОЖНОСТИ РАННЕЙ ДИАГНОСТИКИ ОСТРОГО ИНФАРКТА МИОКАРДА С ПОМОЩЬЮ БЕЛКА, СВЯЗЫВАЮЩЕГО ЖИРНЫЕ КИСЛОТЫ. РОССИЙСКОЕ МНОГОЦЕНТРОВОЕ ИССЛЕДОВАНИЕ ИСПОЛИН - А. И. Мартынов; М. И. Воевода; Г. П. Арутюнов; В. А. Кокорин; А. А. Спасский; А. А. Михайлов (Архивъ внутренней медицины, 2012)
Timely and accurate diagnosis and early start of the treatment can improve the prognosis and clinical course of acute coronary syndrome. In some cases (in the absence of persistent ST-segment elevation, non-specific ECG changes, bundle brunch blocks, atypical presentations of the disease) differential diagnosis between acute myocardial infarction and unstable angina is difficult. The currently applied markers of myocardial necrosis — heart troponins and CK-MB are not effective enough in the early stages of AMI. On results of the multicentre study ISPOLIN, which included 1049 patients in 17 cities of the Russian Federation, the new domestic express-test for the qualitative determination of cardiac fatty acid binding protein, has more sensitivity, accuracy and predictive value compared with the test of the troponin I in the first 12 h of AMI and can be recommended for wide application in practice.